An Investigation into Job Satisfaction and Dissatisfaction among Workers in Local and International Non-Governmental Organization in Sierra Leone - Allieu, Sophie; Moriba, Samba (Technium Business and Management, 2023)
Job satisfaction has been linked to higher productivity and lower turnover in the workplace. Workers who are satisﬁed with their jobs are more inclined to increase output. To develop strategies that address staﬀ welfare concerns, managers must possess the expertise to discern the factors and processes internal and external to employee satisfaction. The study examined job satisfaction and dissatisfaction among workers of non-governmental organizations (NGOs) in Bo, southern Sierra Leone. Embedded mixed methods research design was used to gather qualitative data through interviews and quantitative data using survey questionnaires. Twenty-one Help Salone and Caritas Sierra Leone staﬀ selected randomly from cluster groups participated in the study. Employees were satisﬁed with the human resource policies and beneﬁts of their organizations as well as communications and feedback from managers. They were also very satisﬁed with their healthcare facilities, staﬀ participation and annual leave conditions. Most workers were pleased to perform their daily tasks and, in the process, remain eﬀective and eﬃcient. However, some staﬀ were barely motivated and very few were satisﬁed with the remunerations they received, considering their job responsibilities. Managers could redesign and modify their administrative, ﬁnancial and human resource policies to address job dissatisfaction nuisances in the workplace. Making available policies and guidelines, improving motivation, making remuneration commensurate with workload and conducting general and refresher training for staﬀ would lower turnover, foster productivity and promise sustainability. Therefore, managers of NGOs in Sierra Leone should be reminded from time to time that ensuring lower turnover through best practice could save their organizations the huge cost needed to replace competent workers with high propensity to leave in search of greener pastures.